Work-Related Musculoskeletal Symptoms among Academicians in Malaysian Universities - Syed Abudaheer K.1, Chu Rongle2, Rahul Krishnan Kutty1, Narayanan Muthukumran N.1, Mahendran Jayaram (Institute of Medico-legal Publications Pvt Ltd, 2020)
Work-related musculoskeletal disorder is (WMSD) defined as injuries or disorders of the musculoskeletalsystem, which includes muscles, nerves, tendons, joints, cartilages, and spinal discs that may be associatedwith exposure to risk factors in the workplace. This study is to determine the prevalence of work-relatedmusculoskeletal symptoms and analysis of risk factors among the academicians of university in Malaysia.Index Terms–Academician, Work-related Musculoskeletal Symptom Work-related musculoskeletalsymptoms (WMS) has been identified as “occupational cramps” or “occupational myalgia”, in relation to anoccupation or work-related activities.